Managing thromboembolic risk with menopausal hormone therapy and hormonal contraception in the COVID-19 pandemic: Recommendations from the Spanish Menopause Society, Sociedad Española de Ginecología y Obstetricia and Sociedad Española de Trombosis y Hemostasia. (July 2020) - Ramírez, Isabel; De la Viuda, Esther; Baquedano, Laura; Coronado, Pluvio; Llaneza, Plácido; Mendoza, Nicolás; Otero, Borja; Sánchez, Sonia; Cancelo, Mª Jesús; Páramo, José Antonio; Cano, Antonio
Highlights: For postmenopausal patients in ICU or at high-risk, stop systemic MHT and add LMWH. For low-risk postmenopausal patients, switch to transdermal MHT with LMWH. For perimenopausal patients in ICU, stop CHC and add LMWH. For low-risk perimenopausal patients, switch from CHC to POC and add LMWH. Abstract: COVID-19 is associated with a systemic inflammatory response with activation of coagulation in symptomatic patients. The possibility of coagulopathies in peri- and postmenopausal women taking estrogen therapies makes it necessary to consider antithrombotic strategies, such as the use of low molecular weight heparins (LMWH) at specific prophylactic or treatment doses for each individual case, depending on the risk factors that each woman presents. For such reasons, a panel of experts from various Spanish scientific societies has met to develop usage recommendations for managing menopausal women taking menopausal hormone therapy (MHT) or combined hormonal contraception (CHC) during the COVID-19 pandemic.